2018
DOI: 10.1038/s41467-017-02719-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic stimulation of neuronal activity increases myelination in an axon-specific manner

Abstract: Mounting evidence suggests that neuronal activity influences myelination, potentially allowing for experience-driven modulation of neural circuitry. The degree to which neuronal activity is capable of regulating myelination at the individual axon level is unclear. Here we demonstrate that stimulation of somatosensory axons in the mouse brain increases proliferation and differentiation of oligodendrocyte progenitor cells (OPCs) within the underlying white matter. Stimulated axons display an increased probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
298
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(318 citation statements)
references
References 56 publications
(85 reference statements)
14
298
4
2
Order By: Relevance
“…This observation is in agreement with recent experiments showing that increasing the caliber of normally unmyelinated axons induces their myelination (Goebbels et al, ; Mayoral, Etxeberria, Shen, & Chan, ). However, it disagrees with another recent report showing that neuronal activity does not change the axon diameter of newly myelinated axons (probably glutamatergic; Mitew et al, ). On the basis of these new results, it will be probably necessary to study in details the mechanisms governing the activity‐driven adaptive myelination of specific neuronal subtypes.…”
Section: Gaba In Neuron–oligodendroglia Communicationcontrasting
confidence: 88%
“…This observation is in agreement with recent experiments showing that increasing the caliber of normally unmyelinated axons induces their myelination (Goebbels et al, ; Mayoral, Etxeberria, Shen, & Chan, ). However, it disagrees with another recent report showing that neuronal activity does not change the axon diameter of newly myelinated axons (probably glutamatergic; Mitew et al, ). On the basis of these new results, it will be probably necessary to study in details the mechanisms governing the activity‐driven adaptive myelination of specific neuronal subtypes.…”
Section: Gaba In Neuron–oligodendroglia Communicationcontrasting
confidence: 88%
“…Elimination of neuronal activity by transection of the developing rat optic nerve or by intraocular TTX injection reduces the number of dividing OPCs (Barres & Raff, ), suggesting the neuronal activity is required for proliferation. In accordance with this, electrical, optogenetic, or chemogenetic stimulation of neurons in mice and rats in vivo results in increased proliferation of OPCs in the premotor cortex, the corpus callosum, and the spinal cord, and also reduces the apoptosis of OPC in some conditions (Gibson et al, ; Li, Brus‐Ramer, Martin, & McDonald, ; Mitew et al, ; Nagy et al, ). However, increased proliferation of OPCs was also observed upon sensory deprivation induced by removal of whiskers in neonatal mice (Hill, Patel, Goncalves, Grutzendler, & Nishiyama, ; Mangin et al, ) and accompanied by reduced AMPAR‐mediated thalamocortical synaptic input onto OPCs (Mangin et al, ).…”
Section: Functional Role Of Glutamate Receptors and Glutamatergic Sigmentioning
confidence: 79%
“…Second, some premyelinating processes are retracted from the axons, while others form stable myelin (Czopka, Ffrench-Constant, & Lyons, 2013). Studies using optogenetic or pharmacogenetic (DREADD) treatment to modulate neuronal activity have provided us with important information about activity-dependent myelination (Gibson et al, 2014;Mitew et al, 2018), but it is also important to check whether these results are reproduced under natural physiological conditions. In our study, we successfully observed the full formation of myelin sheaths generated by individual oligodendrocytes after remodeling.…”
Section: Discussionmentioning
confidence: 99%